2022
DOI: 10.1007/s10815-022-02441-z
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte aging: looking beyond chromosome segregation errors

Abstract: The age‐associated decline in female fertility is largely ascribable to a decrease in oocyte quality. This phenomenon is multifaceted and influenced by numerous interconnected maternal and environmental factors. An increase in the rate of meiotic errors is the major cause of the decline in oocyte developmental competence. However, abnormalities in the ooplasm accumulating with age — including altered metabolism, organelle dysfunction, and aberrant gene regulation — progressively undermine oocyte quality. Stock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Consistent with this phenomenon, it has been widely reported that AMA induces aneuploidies, mitochondrial dysfunction, and transcriptional alterations in human oocytes [ 25 27 ]. AMA mouse modeling has further revealed reduced expression in oocytes for genes involved in the establishment and maintenance of DNA methylation, such as Dnmt1 , Dnmt3a , Dnmt3b, and Dnmt3L [ 28 ], along with lower genome-wide DNA methylation in both oocytes and following embryos [ 29 , 30 ]. Meanwhile, with increased maternal age, maternal age-dependent changes have also been observed in the local DNA methylome of human ovarian granulosa cells [ 31 , 32 ], in the specific CpG sites of umbilical cord blood, and even in the specific CpG sites of the peripheral blood of adult daughters [ 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this phenomenon, it has been widely reported that AMA induces aneuploidies, mitochondrial dysfunction, and transcriptional alterations in human oocytes [ 25 27 ]. AMA mouse modeling has further revealed reduced expression in oocytes for genes involved in the establishment and maintenance of DNA methylation, such as Dnmt1 , Dnmt3a , Dnmt3b, and Dnmt3L [ 28 ], along with lower genome-wide DNA methylation in both oocytes and following embryos [ 29 , 30 ]. Meanwhile, with increased maternal age, maternal age-dependent changes have also been observed in the local DNA methylome of human ovarian granulosa cells [ 31 , 32 ], in the specific CpG sites of umbilical cord blood, and even in the specific CpG sites of the peripheral blood of adult daughters [ 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…33 Current models that explain the lower quality of superovulated eggs as reflecting developmental immaturity were based on morphological and biochemical characterization, [34][35][36][37] fertilization and implantation rates, [38][39][40] and oocyte epigenetics. [41][42][43] Final oocyte maturation occurs via nuclear and cytoplasmic changes, 44 requiring correct chromosomal separation 45 and maternal transcript remodeling, [46][47][48] respectively. However, the oocyte can only mature if it establishes correct bi-directional communication with the surrounding cumulus granulosa cells.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased quality of oocytes is considered to be the vital contributor to age‐related declines in fertility, but the problem of maternal age can be effectively abrogated by oocyte donation. For elder women, it has been reported that the defects in meiotic and cytoplasmic ability are associated with oocyte ageing 3,4 . After 35 years, female fertility declines significantly, and approximately 50%–70% of mature oocytes from 40‐year‐old women have chromosomal abnormalities 5 .…”
Section: Introductionmentioning
confidence: 99%
“…For elder women, it has been reported that the defects in meiotic and cytoplasmic ability are associated with oocyte ageing. 3,4 After 35 years, female fertility declines significantly, and approximately 50%-70% of mature oocytes from 40-year-old women have chromosomal abnormalities. 5 Additionally, mitochondrial dysfunction is one of the most notable cytoplasmic changes in aged oocytes and causes decreased cytoplasmic competence.…”
Section: Introductionmentioning
confidence: 99%